Impact of anthropometric adiposity and excessive daytime sleepiness on endothelial function in healthcare workers: A cross-sectional analysis - Damay, Vito; Ivan, Ignatius; Islami, Nadhira A.; Rubismo, Kenza Y. (Narra Sains Indonesia, 2025)
Obesity and excessive daytime sleepiness (EDS) are known contributors to cardiovascular risk through their impact on endothelial function. Healthcare workers, frequently exposed to shift work, are particularly vulnerable to these risk factors. The aim of this study was to assess the relationship between anthropometric adiposity measures and EDS with endothelial function, measured via flow-mediated dilation (FMD), in healthcare workers. This cross-sectional study included 82 healthcare workers aged 20–50 years without pre-existing cardiovascular conditions. Anthropometric measures such as body mass index (BMI), waist circumference (WC), and waist-to-height ratio (WHtR) were collected to assess adiposity. EDS was evaluated using the Epworth sleepiness scale (ESS), with a score ≥10 indicating EDS. Endothelial function was measured via FMD, with values <7.1% indicating dysfunction. Multivariate logistic regression was used to identify predictors of endothelial dysfunction, adjusting for confounders such as age and sex. Collinearity diagnostics, including the Belsley–Kuh–Welsch method, were applied to confirm multicollinearity and refine the regression model. Overweight and obesity, high-risk WC, and increased risk WHtR were associated with endothelial dysfunction (p<0.001), with WHtR showing an independent association (adjusted odds ratio (AOR): 8.48; 95%CI: 2.58–27.86; p<0.001). EDS also showed a significant independent association with impaired FMD outcomes (AOR: 3.73; 95%CI: 1.23–11.26; p=0.020). Pearson correlation analysis revealed significant negative correlations between BMI (r=-0.483, p<0.001), WC (r=-0.473, p<0.001), and WHtR (r=-0.432, p<0.001) with FMD, indicating that higher adiposity levels were linked to poorer endothelial function. Obesity and poor sleep quality, even in the absence of cardiovascular disease, are associated with an increased risk of endothelial dysfunction in healthcare workers. Early intervention focusing on weight management and improving sleep quality could mitigate future cardiovascular risks in this population.